Evaluación del efecto de lipopéptidos antifúngicos producidos por Bacillus Subtilis Ctpx S2-1, en la inducción de expresión de genes de crecimiento y resistencia de Lupinus Mutabilis - Corrales Trávez, Marycruz Karina (2018)
The Andean lupine Lupinus mutabilis Sweet is a legume that, due to its nutritional and traditional value, is widely used in food industry in the Andean region with a growing international projection. However, despite of the high demand that it has its performance is affected by diseases, especially fungi. Among the fungal pathogens that affects the lupine, the anthracnose caused by the fungus Colletotrichum acutatum can significantly reduce production, causing losses greater than 90 Kg ha.1. Generally, these diseases are treated with chemicals in various concentrations, however, the use of environmentally friendly alternatives such as biological control mediated by microorganisms can be efficient for control of the diseases. The biological control of agricultural diseases through the use of bacteria of the genus Bacillus spp. has shown potential for the control of pathogenic fungi of crops and postharvest. Researches about anthracnose control of the Andean lupine demonstrated that different isolates of Bacillus subtilis effectively control infections caused by C. acutatum in the field and in seed during postharvest. Preliminary data of the isolate of Bacillus subtilis Ctpx S2.1 demonstrate that it has a high production capacity of antifungal lipopeptides from the families of surfactin, iturin and fengicin especially at 72 hours of incubation, providing efficacy to counteract the growth of C. acutatum. Other studies has shown that bacteria such as B. subtilis function as plant growth and defense promoters, involving auxin transport genes and related to pathogenesis. Actually, the molecular response generated specifically by L. mutabilis mediated by the interaction of B. subtilis and the lipopeptides has not been clarified. In this context, the objective of this study was to evaluate the changes induced by Bacillus subtilis on the expression of growth and resistance genes of Lupinus mutabilis. Based on the preliminary analysis by HPTLC and PCR, the presence of the families of surfactin, iturin and especially fengicin in the isolate Ctpx S2.1 was confirmed, confirming the production capacity of lipopeptides. The expression of the growth genes AUX1, PIN1, PIN3 and resistance PR.1 was evaluated by relative gene quantification by RT-PCR. The changes were evaluated in gene expression, they were estimated by treatments with a duration of 2.5 hours of suspension of B. subtilis Ctpx S2.1 bacteria with a concentration of 2x106 CFU mL.1, lipopeptide extracts, and control with PBS. The expression of growth and defense genes was positive especially in the treatment with the bacterial suspension compared to the control. Likewise, effectiveness tests were carried out to verify the physiological responses generated by the plant in the presence of experimental treatments, where, with the exception of stem length, treatments showed no significant difference in the chlorophyll index, humidity and length percentage of the root.Our results support that biocontrol potential of B. subtilis CTpxS2.1 through lipopeptides production play a major role in expression of growth and defense genes of L. mutabilis.